7. Management of CBD stones-a comparative study of ERCP guided CBD stone removal and open surgery. - Dr. Hitendra Desai (BJ Kines: National Journal of Basic & Applied Sciences, 2019)
Background and objectives :- to review the patients who underwent open surgery or endoscopy for common bile duct stone removal. To compare the efficacy of open surgery versus endoscopy in terms of achievement of common bile duct clearance with respect to the size of the stone, to compare the efficacy in terms of achievement of regression of symptoms, signs and biochemical parameters and post operative complications and incidence of mortality. Material and method:- this is a prospective study of management of 40 cases of cbd stones, performed in the surgery department of civil hospital, ahmedabad. Result:- open surgery is better than ercp in terms of improvement of symptoms and lab parameters (95%>80%), morbidity and duct clearance (95%>80%). Conclusion:- open surgery is more efficacious than ercp in terms of achievement of common bile duct clearance, safer than ercp in terms of minor morbidity, in terms of achievement of regression of symptoms, signs and biochemical parameters for common bile duct calculi. Open surgery and ercp are comparable in terms of major morbidity. Ercp is safer than open surgery in terms of incidence of mortality.